Identification of strategic factors of profitability in the Andalusian rural savings banks - Maria Asuncion Gravalos; Ignacio Pomares (European Regional Science Association (ERSA), 1998)
The Rural Savings Banks (cajas rurales), although in their origin they played a primordial role in the financing of the agricultural sector and of the rural context in general, at the moment they are present in a wide variety of managerial sectors, thanks to an intense politics of diversification of their activity. These entities constitute the most excellent group inside the Spanish cooperative banking, so much for their territorial covering as for the volume of own and other people's resources. In this work we try to discover which strategy has been adopted by the sector of the Rural Savings Banks of Andalusia for the attainment of its objectives of profitability. In this paper we have elaborated it a methodology that allows us to carry out an analysis of the factors of profitability applying it to this sector. Finally conclusions are extracted.
Keywords: 330